DOCUMENTING COMPETENCE: EVIDENCE OF EXCELLENCE IN NURSE ANESTHESIA PRACTICE - Rizer, Carol (European Scientific Journal, ESJ, 2015)
Sweeping changes in the healthcare environment reveal a greater need for the placement of qualified, cost-effective providers in all areas. Certified Registered Nurse Anesthetists (CRNAs) have a proven track record of safety. However, a gap exists in identifying, quantifying, and linking existing practice evidence to the performance of individual CRNAs. The purpose of this project was to develop a practice portfolio for each CRNA that would provide evidence of competent performance in a rural acute care setting. The project demonstrated that CRNA practice portfolios can be utilized to demonstrate competent practice through the compilation of objective and quantifiable evidence.